Age Influences Loss Aversion Through Effects on Posterior Cingulate Cortical Thickness - Guttman, Zoe R.; Ghahremani, Dara G.; Pochon, Jean-Baptiste; Dean, Andy C.; London, Edythe D. (Frontiers in Neuroscience, 2021)
Decision-making strategies shift during normal aging and can profoundly affect wellbeing. Although overweighing losses compared to gains, termed “loss aversion”, plays an important role in choice selection, the age trajectory of this effect and how it may be influenced by associated changes in brain structure remain unclear. We therefore investigated the relationship between age and loss aversion, and tested for its mediation by cortical thinning in brain regions that are susceptible to age-related declines and are implicated in loss aversion ― the insular, orbitofrontal, and anterior and posterior cingulate cortices. Healthy participants (n=112, 17-54 years) performed the Loss Aversion Task. A subgroup (n=78) provided structural magnetic resonance imaging scans. Loss aversion followed a curvilinear trajectory, declining in young adulthood and increasing in middle-age, and thinning of the posterior cingulate cortex mediated this trajectory. The findings suggest that beyond a threshold in middle adulthood, atrophy of the posterior cingulate cortex influences loss aversion.